Business Development Strategy Dahan Coffee using SWOT analysis and QSPM - Irawan, Siti Maulani; Herlinawati, Erna (Dinasti International Journal of Digital Business Management, 2025)
Dahan Coffee is a cafe business that continues to grow in the midst of competition in the culinary industry. This research aims to formulate a business development strategy for Dahan Coffee using SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) analysis. This research method involves collecting primary data through interviews and observations, as well as secondary data from company reports and related literature. SWOT analysis was used to identify internal and external factors affecting the business, while QSPM was applied to prioritize strategies based on the relative attractiveness of each strategy alternative. The results show that Dahan Coffee has strengths in consistent product quality and strategic location, but faces challenges in the form of high competition and limited production capacity. The main opportunities include increasing coffee consumption trends with digital marketing and potential collaboration with local communities, while the main threat is changing consumer preferences. Based on QSPM analysis, the recommended priority strategies are product diversification and increased digital marketing activities. The implementation of these strategies is expected to improve Dahan Coffee's competitiveness and business growth in the future.